MEMBANGUN KEPERCAYAAN DIRI SISWA MELALUI PEMBELAJARAN MATEMATIKA HUMANIS (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2014)
One of the functions of education is a process of personal formation. Thus education should be able to play a role in preparing students to build a personality, and growing nation and character building, including the vision, commitment, consistency and responsibility. Learning mathematics humanist implemented by teachers with students in the classroom plays an important role in the formation of character. These lessons will shape human values in students. In addition to understanding and mastering math concepts, students will be trained to work independently as well as work in teams, to be critical, creative, consistent, logical, systematic, value the opinions, honest, confident, and responsible. Ease in learning mathematics can make students appreciate and love math. With the interest in learning mathematics makes students confident that any difficult lessons can be learned. Salah satu fungsi pendidikan adalah sebagai proses pembentukan pribadi. Dengan demikian pendidikan harus mampu berperan dalam menyiapkan peserta didik membangun kepribadian, dan menumbuhkan nation and character building, diantaranya adalah  memiliki visi, komitmen, konsisten dan tanggung jawab. Pembelajaran matematika humanis  yang dilaksanakan oleh guru bersama siswa di kelas memegang peranan penting pada pembentukan karakter. Pembelajaran ini akan membentuk nilai-nilai kemanusiaan dalam diri siswa. Selain memahami dan menguasai konsep matematika, siswa akan terlatih bekerja mandiri maupun bekerjasama dalam kelompok, bersikap kritis, kreatif, konsisten, berpikir logis, sistematis, menghargai pendapat, jujur, percaya diri, dan bertanggung jawab. Kemudahan dalam mempelajari matematika dapat membuat siswa menghargai dan mencintai matematika. Dengan adanya ketertarikan dalam belajar matematika membuat siswa percaya diri bahwa pelajaran sesulit apapun dapat dipelajarinya.
Keywords: matematika humanis; pembangunan karakter; kepercayaan diri; character building; humanis mathmatics; self confidence